2021
DOI: 10.1111/tbed.13986
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of African swine fever virus from domestic pigs in India

Abstract: African swine fever (ASF) is the most dreaded disease of pigs, which can cause mortality of up to 100%. Following disease outbreaks with high mortality in pigs in two states of north‐east India, namely Arunachal Pradesh and Assam in early 2020, we confirmed the first occurrence of African swine fever (ASF) in domestic pigs in India by real‐time PCR, virus isolation and nucleotide sequencing. Genetic analyses in three independent genomic regions (B646L gene encoding the p72 protein, E183L gene encoding the p54 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 10 publications
2
30
0
Order By: Relevance
“…With 10 aa tetramer repeats in CVR (BNDBNDBNAA), the ASFV strains in this study were classi ed into subgroup XXXII, along with the ASFV isolates in circulation in Vietnam (2019), the Chinese ASFV strains from outbreaks in 2018-2019, and other strains in Europe. At the same time, a study in India that performed B602L variable region analysis also showed that the tetrameric aa repeats in CVR are similar to other post-2007-p72-genotype II viruses reported from other Asian and European countries [30]. Although analysis of the CVR has identi ed it as the most variable genome region, Estonia isolates, belonging to the same genotype II classi cation based on the p72 genes and showing no difference in size and aa tetramers in the CVR genes, had the aa change of Y instead of C compared with the reference strain (Georgia_2007/1) [31].…”
Section: Discussionsupporting
confidence: 68%
“…With 10 aa tetramer repeats in CVR (BNDBNDBNAA), the ASFV strains in this study were classi ed into subgroup XXXII, along with the ASFV isolates in circulation in Vietnam (2019), the Chinese ASFV strains from outbreaks in 2018-2019, and other strains in Europe. At the same time, a study in India that performed B602L variable region analysis also showed that the tetrameric aa repeats in CVR are similar to other post-2007-p72-genotype II viruses reported from other Asian and European countries [30]. Although analysis of the CVR has identi ed it as the most variable genome region, Estonia isolates, belonging to the same genotype II classi cation based on the p72 genes and showing no difference in size and aa tetramers in the CVR genes, had the aa change of Y instead of C compared with the reference strain (Georgia_2007/1) [31].…”
Section: Discussionsupporting
confidence: 68%
“…ASF is registered as one of the most important transboundary animal diseases (TADs), notifiable to OIE, and the wide recurrence of outbreaks in various regions of the world indicates that many questions are still poorly solved concerning the biology of this devastating disease. The ASFV strains circulating in Europe and Asia are of p72 genotype II (Gallardo et al., 2014; Ge et al., 2018; Kim et al., 2020; Mai et al., 2021; Malogolovkin et al., 2019; Rajukumar et al., 2021; Vilem et al., 2020), which are generally highly virulent both in domestic pigs and wild boar causing acute disease with almost 100% lethality in animals of all ages and sexes (Blome et al., 2020; Pikalo et al., 2019, 2020). However, one major concern is its increasing and continuous trend to appear and reappear in a clinically very mild or in a completely unapparent form in areas where the disease is endemic (Lamberga et al., 2018, 2020; Nurmoja et al., 2020; Sánchez‐Vizcaíno et al., 2012, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…ASF is registered as one of the most important transboundary animal diseases (TADs), notifiable to OIE, and the wide recurrence of outbreaks in various regions of the world indicates that many questions are still poorly solved concerning the biology of this devastating disease. The ASFV strains circulating in Europe and Asia are of p72 genotype II (Gallardo et al, 2014;Ge et al, 2018;Kim et al, 2020;Mai et al, 2021;Malogolovkin et al, 2019;Rajukumar et al, 2021;Vilem et al, 2020), which are generally highly virulent both in domestic pigs and TA B L E 5 African swine fever virus (ASFV) comparative antibody detection in serum samples by ELISA and IPT indicated the first positive finding in days ± standard deviation (SD) and the percentage of positives domestic pigs 7± 0 (50%) 16 ± 0 (50%) 16 ± 0 (75%) Lv17/WB/Rie1 10 (100%) 7± 0 (100%) 19.5 ± 3.6 (100%) 19.5 ± 3.6 (100%) wild boar causing acute disease with almost 100% lethality in animals of all ages and sexes (Blome et al, 2020;Pikalo et al, 2019Pikalo et al, , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the genetic basis for ASFV spread and adaptation among hosts will facilitate vaccine development (Bao et al, 2021). As reported in this Special Issue, ASFV genotype II isolates identical to those isolated in China and Russia have also been found in Mongolia (Ankhanbaatar et al, 2021), in India (Rajukumar et al, 2021) and in Indonesia (Indi Dharmayanti et al, 2021), although ASFV variants in the domestic pig population in Vietnam have also been detected (Tran et al, 2021). Monitoring the genetic characteristics of ASFV isolates is needed to understand the spread of this disease across countries (Minoungou et al, 2021).…”
mentioning
confidence: 89%